A dual-activity topoisomerase complex regulates mRNA translation and turnover. Issue 12 (24th June 2022) - Su, Shuaikun; Xue, Yutong; Sharov, Alexei; Zhang, Yongqing; Lee, Seung Kyu; Martindale, Jennifer L; Li, Wen; Ku, Wai Lim; Zhao, Keji; De, Supriyo; Shen, Weiping; Sen, Payel; et al.
Abstract: Topoisomerase 3β (TOP3B) and TDRD3 form a dual-activity topoisomerase complex that interacts with FMRP and can change the topology of both DNA and RNA. Here, we investigated the post-transcriptional influence of TOP3B and associated proteins on mRNA translation and turnover. First, we discovered that in human HCT116 colon cancer cells, knock-out (KO) of TOP3B had similar effects on mRNA turnover and translation as did TDRD3-KO, while FMRP-KO resulted in rather distinct effects, indicating that TOP3B had stronger coordination with TDRD3 than FMRP in mRNA regulation. Second, we identified TOP3B-bound mRNAs in HCT116 cells; we found that while TOP3B did not directly influence the stability or translation of most TOP3B target mRNAs, it stabilized a subset of target mRNAs but had a more complex effect on translation–enhancing for some mRNAs whereas reducing for others. Interestingly, a point mutation that specifically disrupted TOP3B catalytic activity only partially recapitulated the effects of TOP3B-KO on mRNA stability and translation, suggesting that the impact of TOP3B on target mRNAs is partly linked to its ability to change topology of mRNAs. Collectively, our data suggest that TOP3B–TDRD3 can regulate mRNA translation and turnover by mechanisms that are dependent and independent of topoisomerase activity.